Metagenomic next-generation sequencing for the etiological diagnosis of rabies virus in cerebrospinal fluid - Liu, Yong; Mo, Xichao; Feng, Ye; Willoughby, Rodney E.; Weng, Xing; Wang, Yuyang; Li, Xing; Gao, Junling; Tian, Jinfei; Peng, Jie (Frontiers in Medicine, 2023)
Abstract: Background: Rabies is a highly fatal disease. Once symptoms develop, death usually occurs within days. Survivors were occasionally reported in the literatures. Ante-mortem diagnosis remains a challenge in most rabies endemic countries. A novel, accurate diagnostic assay is highly desirable. Methods: We used metagenomic next-generation sequencing (mNGS) to examine the cerebrospinal fluid (CSF) samples of a 49-year-old patient with rabies and validated the results by TaqMan PCR and RT-PCR/Sanger sequencing. Results: mNGS identified sequence reads uniquely aligned to the rabies virus (RABV). PCR confirmed the presence of the partial RABV N gene in the CSF. Phylogenetic analysis showed that the RABV grouped as an Asian clade, which is the most broadly distributed clade in China. Conclusions: mNGS may be a useful screening tool for the etiological diagnosis of rabies, especially in the absence of timely rabies laboratory testing or in patients with no exposure history.